Pelatihan manajemen bencana terhadap kesiapsiagaan pada mahasiswa: A literature review - Mufimah, Mufimah; Kamaludin, Ridlwan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Disaster preparedness training has now begun to be developed from elementary to higher education, namely students, with the aim of building a culture of safety and resilience in the younger generation. Universities through the tridharma of higher education have a strategic role in disaster management through learning, research and community service. This role can take place with the active participation of lecturers and students. Purpose: To examine the effect of disaster management training on student preparedness. Method: Literature review research with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach and using PICO. The search databases used were Pubmed/NCBI, Scopus, and Sciencedirect with the keywords